1993
DOI: 10.2105/ajph.83.6.851
|View full text |Cite
|
Sign up to set email alerts
|

From beer to crack: developmental patterns of drug involvement.

Abstract: OBJECTIVES. Prior research has identified developmental stages in drug use in adolescence, from substances that are legal for adults to illicit drugs. The position of crack in patterns of drug involvement remains to be established. METHODS. The analyses are based on a sample (n = 1108) representative of 12th graders attending New York State public and private schools. From reported ages of first use of five classes of drugs (alcoholic beverages, cigarettes, marijuana, cocaine but not crack, crack), alternate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
2
23

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(252 citation statements)
references
References 16 publications
12
215
2
23
Order By: Relevance
“…This may support a theory that perceptions surrounding a drug type and use, e.g., 'crackhead,' impacts age at initiation. Overall, this pattern of age at initiation of various drugs challenge theories which propose that 'soft', lower risk drug use precedes or is a gateway to 'hard', higher risk drug use (Kandel, 1975;Kandel and Yamaguchi, 1993). In addition, it raises the question of how the 'hard'/'soft' drug distinction applies to ketamine, and other drugs, such as ecstasy and GHB.…”
Section: Discussionmentioning
confidence: 91%
“…This may support a theory that perceptions surrounding a drug type and use, e.g., 'crackhead,' impacts age at initiation. Overall, this pattern of age at initiation of various drugs challenge theories which propose that 'soft', lower risk drug use precedes or is a gateway to 'hard', higher risk drug use (Kandel, 1975;Kandel and Yamaguchi, 1993). In addition, it raises the question of how the 'hard'/'soft' drug distinction applies to ketamine, and other drugs, such as ecstasy and GHB.…”
Section: Discussionmentioning
confidence: 91%
“…Among individual factors, use of licit substances Gilvarry, 2000;Guxens et al, 2007aGuxens et al, , 2007bKandel and Yamaguchi, 1993;Vega and Gil, 2005;Wittchen et al, 2007) has been reported consistently as a risk factor for subsequent use of illicit drugs. Characteristics related broadly to externalizing behaviors, such as impulsivity (Conway et al, 2003), early behavior problems (Kreek et al, 2005), as well as behavioral and emotional symptoms (Brook et al, 1996;Buckner et al, 2008;Jane-Llopis and Matytsina, 2006;Monshouwer et al, 2006;White et al, 2001;Wittchen et al, 2007) have been identified as risk factors for drug use.…”
Section: Introductionmentioning
confidence: 99%
“…The low self-report and urinalysis biases for cannabis are an indication that few juveniles who use it will be overlooked by either approach to detection. Because cannabis use often leads to more serious drug use (Kandel and Yamaguchi, 1993;Kandel, 1984a, 1984b), almost all youth entering detention can be considered at risk for developing substance use problems.…”
Section: Discussionmentioning
confidence: 99%